2020
DOI: 10.1007/s11657-020-0706-y
|View full text |Cite
|
Sign up to set email alerts
|

Fragility fractures in Europe: burden, management and opportunities

Abstract: This report provides an overview and a comparison of the burden and management of fragility fractures in the largest five countries of the European Union plus Sweden (EU6). In 2017, new fragility fractures in the EU6 are estimated at 2.7 million with an associated annual cost of €37.5 billion and a loss of 1.0 million quality-adjusted life years. Introduction Osteoporosis is characterized by reduced bone mass and strength, which increases the risk of fragility fractures, which in turn, represent the main conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
389
2
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 462 publications
(417 citation statements)
references
References 56 publications
(58 reference statements)
7
389
2
19
Order By: Relevance
“…The tremendous economic impact of osteoporotic fractures (7)(8)(9) and development of comorbidities after fracture (10)(11)(12) highlight the need to understand the genetic, cellular, and endocrine mechanisms that influence bone mass. With the renewed interest in intermediary metabolism in cancer (13)(14)(15) and the recognition that bone is not merely a structural organ acting as a reserve of minerals but also an endocrine organ that can influence systemic metabolism (16)(17)(18)(19)(20)(21), research in the field of skeletal biology has coalesced over the last few years on the contributions of cellular metabolism to osteoblast function and bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…The tremendous economic impact of osteoporotic fractures (7)(8)(9) and development of comorbidities after fracture (10)(11)(12) highlight the need to understand the genetic, cellular, and endocrine mechanisms that influence bone mass. With the renewed interest in intermediary metabolism in cancer (13)(14)(15) and the recognition that bone is not merely a structural organ acting as a reserve of minerals but also an endocrine organ that can influence systemic metabolism (16)(17)(18)(19)(20)(21), research in the field of skeletal biology has coalesced over the last few years on the contributions of cellular metabolism to osteoblast function and bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is therefore a major health problem, as it not only affects the health and quality of the life of sufferers, but also there are the negative impacts of the associated economic costs and the social problems of treatment. In 2010, the International Osteoporosis Foundation (IOF), together with the European Federation of Pharmaceutical Industry Associations (EFPIA), described the economic burden of the disease in the countries of the European Union and concluded that osteoporosis, as a whole (fractures, drug treatment and long-term care) costs 37 billion euros annually, and will increase by 25% in 2025 [5].…”
Section: Introductionmentioning
confidence: 99%
“…The number of fragility fractures and cases of osteoporosis is increasing worldwide, creating an increasing burden to society. [2] The risk of refracture is highest immediately after a fracture. This suggests that there is an opportunity to optimize the benefits of fracture prevention by treating patients as soon as possible after occurrence of a fracture.…”
mentioning
confidence: 99%
“…In France, Sweden, and Spain, 85%, 84%, and 72% of fracture patients remained untreated one year after fracture, respectively. [2] Citation: Atik OŞ, Aslan A, Odluyurt M. Are fragility fractures being treated properly? Jt Dis Relat Surg 2020;31(2):403-404.…”
mentioning
confidence: 99%
See 1 more Smart Citation